Manufacturing method of wick and vapor chamber

The method of forming wrinkled structures and micro-nanoparticles through laser scanning has improved the hydrophilic performance of the liquid absorbing core, solved the problem that the existing liquid absorbing core is difficult to meet the high-energy heat dissipation needs, and achieved a more efficient heat dissipation effect.

CN119394069APending Publication Date: 2025-02-07DONGGUAN LINGJIE PRECISION MACHINING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411652717.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing liquid absorbent core has limited hydrophilic properties and is difficult to meet the needs of higher energy heat dissipation.

Method used

By scanning the surface of the stainless steel mesh with a laser, a wrinkle-like structure and multiple micro-nanoparticles are formed, thereby improving the hydrophilicity of the liquid absorbent core.

Benefits of technology

The hydrophilic performance of the liquid absorbent core is improved, and can meet the heat dissipation needs of higher energy. Compared with the existing technology, the process is less difficult, more efficient, less costly, and more environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119394069A_ABST
    Figure CN119394069A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a manufacturing method of a wick and a vapor chamber. The manufacturing method comprises the following steps: providing a stainless steel mesh; and a laser is adopted to scan the surface of the stainless steel mesh, so that a wrinkle-shaped structure and a particle structure are formed on the surface of the stainless steel mesh. The manufacturing method of the wick provided by the embodiment of the invention at least has the following beneficial effects that the laser is adopted to scan the surface of the stainless steel mesh, so that a hydrophilic wrinkle-shaped structure and a plurality of micro-nano particles are formed on the surface of the stainless steel mesh, the hydrophilic performance of the wick is improved, and the wick is more compact. And the heat dissipation requirement with higher energy can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of liquid absorbent core manufacturing, in particular to a method for manufacturing a liquid absorbent core and a temperature equalizing plate. Background Art

[0002] Stainless steel mesh is widely used in the preparation of liquid absorbent cores due to its low price, stable properties and good hydrophilic properties. The liquid absorbent cores prepared by stainless steel mesh have good heat-relieving properties. The liquid absorbent cores quickly absorb liquid and form reflux with the temperature plate, quickly taking away the heat, absorbing it and dissipating it. As the battery capacity and heat dissipation energy demand increase, the liquid absorbent core needs to absorb the reflux liquid faster to meet the higher energy heat dissipation needs. The existing liquid absorbent cores have limited hydrophilic properties and are difficult to meet the higher energy heat dissipation needs. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a method for manufacturing a liquid absorbent core and a temperature averaging plate, which can improve the hydrophilicity of the liquid absorbent core and meet the heat dissipation requirements of higher energy.

[0004] In a first aspect, an embodiment of the present invention provides a method for manufacturing a liquid-absorbing core, the manufacturing method comprising: providing a stainless steel mesh; scanning the surface of the stainless steel mesh with a laser so that the surface of the stainless steel mesh forms a wrinkled structure and a granular structure.

[0005] The method for manufacturing the liquid absorbent core provided in the first aspect of the present invention has at least the following beneficial effects:

[0006] By scanning the surface of the stainless steel mesh with a laser, a hydrophilic wrinkled structure and a plurality of micro-nano particles are formed on the surface of the stainless steel mesh, thereby improving the hydrophilicity of the liquid wick and meeting the heat dissipation requirements of higher energy.

[0007] In an example of this implementation manner, the laser scans the surface of the stainless steel mesh 1-7 times.

[0008] In an example of this implementation, the laser pulse width of the laser is 1 μs-120 μs.

[0009] In an example of this implementation, the frequency of the laser is 80KHz-300KHz.

[0010] In an example of this implementation, the scanning speed of the laser is 1000 mm / s-15000 mm / s.

[0011] In an example of this implementation manner, before scanning the surface of the stainless steel mesh with a laser, the process includes: ultrasonically cleaning the stainless steel mesh.

[0012] In an example of this implementation manner, after the ultrasonic cleaning of the stainless steel mesh, the method further comprises: drying the stainless steel mesh.

[0013] In an example of this implementation manner, providing a stainless steel mesh includes: cutting the stainless steel mesh into a shape of a liquid wick.

[0014] In an example of this implementation manner, the particle size of the micro-nano particles is less than 500 μm.

[0015] In a second aspect, an embodiment of the present invention provides a temperature equalizing plate, which includes a liquid wick prepared by the manufacturing method described in any example of the implementation of the first aspect.

[0016] The temperature homogenizing plate provided in the second aspect of the present invention has at least the following beneficial effects:

[0017] By adding the liquid absorbent core prepared by the manufacturing method of the first embodiment to the temperature equalizing plate, the temperature equalizing plate can obtain higher heat dissipation efficiency without changing its volume, and can better adapt to the increasingly higher heat dissipation requirements.

[0018] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0020] Figure 1 is a flow chart of a method for making a liquid absorbent core provided in an embodiment of the present invention;

[0021] Figure 2 yes Figure 1 A schematic diagram of the scanning path in step S102;

[0022] Figure 3a to Figure 3c This is a schematic diagram of the stainless steel mesh before laser scanning;

[0023] Figures 4a to 4e This is a schematic diagram of the stainless steel mesh after laser scanning;

[0024] Figure 5 yes Figure 4e Annotated schematic diagram. DETAILED DESCRIPTION

[0025] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0026] In the description of the present invention, it should be understood that descriptions involving orientations, such as up, down, front, back, left, right, etc., and orientations or positional relationships indicated are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0027] In the description of the present invention, "several" means more than one, "many" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing the technical features, and cannot be understood as indicating or implying the relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0028] In the description of the present invention, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention based on the specific content of the technical solution.

[0029] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0030] In the prior art, in order to improve the hydrophilicity of the stainless steel absorbent core, it is usually sintered on a substrate. During the sintering process, the hydrophobic impurities on the surface of the stainless steel absorbent core are removed by high temperature, and its own structure has a certain hydrophilicity, but the hydrophilicity is limited and it is difficult to meet the heat dissipation requirements of higher energy. At present, the stainless steel absorbent core can meet the heat dissipation requirements of 2-3W power after sintering and packaging. With the increase of battery capacity and required heat dissipation energy, the current structure of the stainless steel absorbent core is not enough to meet the heat dissipation requirements of higher energy. Changing the structure of the stainless steel absorbent core to improve its hydrophilicity is a current research hotspot. In addition to sintering, there are other ways, such as electroplating stainless steel absorbent core to improve hydrophilicity, but the process is cumbersome, inefficient, not easy to industrialize, and has large pollution. Therefore, how to be efficient, industrialized and change the structure of the stainless steel absorbent core, fundamentally improving the hydrophilicity of the stainless steel absorbent core is a top priority.

[0031] See also Figures 1 to 4e , Figure 1 is a flow chart of a method for making a liquid absorbent core provided in an embodiment of the present invention; Figure 2 yes Figure 1 A schematic diagram of the scanning path in step S102; Figure 3a to Figure 3c This is a schematic diagram of the stainless steel mesh before laser scanning;

[0032] Figures 4a to 4e This is a schematic diagram of the stainless steel mesh after laser scanning. Figures 4a to 4c This is a schematic diagram of the same position of the stainless steel mesh at different magnification levels. Figure 4d to Figure 4f Schematic diagrams of the same position of the stainless steel mesh at different magnification levels. An embodiment of the present invention provides a method for making a liquid wick, the method comprising:

[0033] S101: Provide stainless steel mesh;

[0034] S102: Scanning the surface of the stainless steel mesh with a laser to form a wrinkled structure and a plurality of micro-nano particles on the surface of the stainless steel mesh.

[0035] For details, please refer to Figure 2 In step S102, the scanning path of the laser on the surface of the stainless steel mesh is to meander along the first direction on the plane where the stainless steel mesh is located, and extend along the second direction perpendicular to the first direction to basically cover the stainless steel mesh. The scanning of the stainless steel mesh is relatively uniform, which is conducive to obtaining a relatively hydrophilic wick at all locations. The laser is preferably a nanosecond ultraviolet laser to output high-energy ultraviolet light to the stainless steel mesh, which can better form a pleated structure and multiple micro-nano particles.

[0036] Specifically, in this embodiment, the scanning path is: the laser enters the stainless steel mesh from the left position on the bottom side of the stainless steel mesh, and extends to the top side along the length direction of the stainless steel mesh, and then extends a certain distance along the width direction of the stainless steel mesh, and then extends back to the bottom side along the length direction of the stainless steel mesh, and repeats this process to form a circuitous and extended scanning path, which can basically cover the stainless steel mesh and scan the stainless steel mesh evenly.

[0037] For details, please refer to Figure 5 , Figure 5 yes Figure 4e Schematic diagram of the annotation, Figure 5 100 is a stainless steel mesh, 10 is micro-nano particles, and 20 is a pleated structure. In this embodiment, the stainless steel mesh 100 is a mesh structure that is staggered horizontally and vertically. The micro-nano particles 10 and the pleated structure 20 are distributed on the surface of the stainless steel mesh 100. The pleated structure 20 can be understood as relatively raised ribs. Some of the micro-nano particles 10 are arranged on the surface of the stainless steel mesh 100, and some of the micro-nano particles 10 are arranged on the pleated structure 20.

[0038] It is understandable that the surface of the stainless steel mesh before laser scanning is smooth and relatively hydrophobic, so the hydrophilicity of the obtained liquid absorbent core is weak and it is difficult to meet the high-energy heat dissipation requirements. However, the surface of the stainless steel mesh after laser scanning has a wrinkled structure and multiple micro-nano particles, which can be better attached by water, thereby improving the hydrophilicity.

[0039] The method for manufacturing the liquid absorbent core provided in the embodiment of the present invention has at least the following beneficial effects:

[0040] By using a laser to scan the surface of the stainless steel mesh, a hydrophilic folded structure and multiple micro-nano particles are formed on the surface of the stainless steel mesh, which improves the hydrophilicity of the liquid-absorbing core and can meet the heat dissipation requirements of higher energy. In addition, compared with the existing sintering or electroplating methods, the process using laser scanning is less difficult, more efficient, less costly, and more environmentally friendly.

[0041] In one example of this implementation, the number of times the laser scans the surface of the stainless steel mesh is 1-7 times. By setting the number of times the laser scans the surface of the stainless steel mesh to 1-7 times, micro-nano particles and a pleated structure can be fully formed on the surface of the stainless steel mesh to ensure that the wick has good hydrophilic properties.

[0042] It is understandable that micro-nanoparticles and wrinkled structures are formed simultaneously during the scanning process, and in terms of improving the hydrophilicity, the effect of micro-nanoparticles is greater than that of wrinkled structures. Therefore, the scanning step needs to make the proportion of micro-nanoparticles as high as possible to obtain better hydrophilicity.

[0043] Specifically, the number of scans is preferably 2-7 times. When the number of scans is less than 2 times, the surface of the stainless steel mesh cannot be fully melted, it is difficult to form micro-nano particles, and the proportion of micro-nano particles is too low. When the number of scans is greater than 7 times, the surface of the stainless steel mesh is difficult to cool quickly, and particle growth occurs, which also leads to a too low proportion of micro-nano particles, and it is easy to damage the structure of the stainless steel mesh itself, resulting in product scrapping. By setting the number of scans to 2-7 times, the surface of the stainless steel mesh can be fully melted and quickly cooled, and micro-nano particles can be better formed, the proportion of micro-nano particles is high, and the hydrophilic property is ideal.

[0044] In one embodiment of this embodiment, the laser pulse width of the laser is 1μs-120μs. It is understandable that when the laser pulse width is greater than 120μs, the heat accumulation is too large, and overburning is likely to occur, resulting in the surface of the stainless steel mesh being unable to cool in time, which is not conducive to the formation of micro-nano particles. When the laser pulse width is less than 1μs, the heat accumulation is too small, and the surface of the stainless steel mesh is difficult to fully melt (can only slightly melt), which is also not conducive to the formation of micro-nano particles. By setting the laser pulse of the laser to 1μs-120μs, the surface of the stainless steel mesh can be fully melted and quickly cooled, which is conducive to the formation of micro-nano particles, increasing the proportion of micro-nano particles, and improving hydrophilic properties.

[0045] In one embodiment of this embodiment, the frequency of the laser is 80KHz-300KHz. It is understandable that when the frequency of the laser is less than 80KHz, the heat accumulation is too large, and overburning is prone to occur, resulting in the surface of the stainless steel mesh being unable to cool in time, which is not conducive to the formation of micro-nano particles. When the frequency of the laser is greater than 300KHz, the output energy is insufficient, resulting in the surface of the stainless steel mesh being unable to fully melt (only slightly melted), which is also not conducive to the formation of micro-nano particles. By setting the frequency of the laser to 80KHz-300KHz, the surface of the stainless steel mesh can be fully melted and rapidly cooled, so as to facilitate the formation of micro-nano particles, increase the proportion of micro-nano particles, and enhance hydrophilic properties.

[0046] In one embodiment of this embodiment, the scanning speed of the laser is 1000mm / s-15000mm / s. It is understandable that when the scanning speed of the laser is less than 1000mm / s, the scanning speed is too slow, the heat accumulation on the stainless steel mesh is too high, the surface of the stainless steel mesh is over-melted, and it is difficult to cool in time, which is not conducive to the formation of micro-nano particles. When the scanning speed of the laser is greater than 15000mm / s, the heat accumulation on the stainless steel mesh is too low, the surface of the stainless steel mesh can only be slightly melted, and cannot be fully melted, which is also difficult to form micro-nano particles. By setting the scanning speed of the laser to 1000mm / s-15000mm / s, the surface of the stainless steel mesh can be fully melted and quickly cooled, so as to facilitate the formation of micro-nano particles, increase the proportion of micro-nano particles, and enhance hydrophilic properties.

[0047] In one embodiment of this implementation, S102: before scanning the surface of the stainless steel mesh with a laser, the method includes:

[0048] S102a: Ultrasonic cleaning of stainless steel mesh.

[0049] Specifically, an ultrasonic cleaning machine can be used to clean the stainless steel mesh. This arrangement allows for better formation of a wrinkled structure and a plurality of micro-nano particles on the stainless steel mesh through laser scanning.

[0050] In one embodiment of this implementation mode, S102a: after ultrasonic cleaning of the stainless steel mesh, the method includes:

[0051] S102b: Drying the stainless steel mesh.

[0052] Specifically, a hair dryer can be used to dry the stainless steel mesh. This arrangement facilitates better formation of a wrinkled structure and a plurality of micro-nano particles on the stainless steel mesh through laser scanning.

[0053] In one example of this implementation mode, S101: providing a stainless steel mesh, including:

[0054] S1011: Cut the stainless steel mesh into the shape of the wick.

[0055] Specifically, a cutting machine can be used to cut the stainless steel mesh, so as to better form a wrinkled structure and a plurality of micro-nano particles on the stainless steel mesh through laser scanning.

[0056] In one embodiment of this implementation mode, the particle size of the micro-nanoparticles is less than 500μm. Specifically, the micro-nanoparticles include nanoparticles and micron particles. The specific surface area of ​​the nanoparticles is larger than that of the micron particles, and the specific surface area of ​​the micron particles is larger than that of the wrinkled structure. The larger specific surface area is more convenient for water to adhere to, and the hydrophilic property can be more fully improved. In this embodiment, the particle size of the nanoparticles is 1nm-1000nm, and the particle size of the micron particles is 1μm-1000μm. Usually, the particle size of the nanoparticles is 50nm-500nm, and the particle size of the micron particles is 50μm-500μm. It can be understood that the particle size of the micro-nanoparticles is limited to less than 500μm, and the proportion of nanoparticles is relatively high, which can further improve the hydrophilic property.

[0057] In this embodiment, the method for making the liquid absorbent core is as follows:

[0058] (1) cutting the stainless steel mesh by a cutting machine to cut the stainless steel mesh into the shape of a wick;

[0059] (2) Using an ultrasonic cleaning machine to clean the cut stainless steel mesh to remove impurities such as oil stains on the stainless steel mesh;

[0060] (3) Use a hair dryer to dry the cleaned stainless steel mesh;

[0061] (4) A nanosecond ultraviolet laser is used to scan the dried stainless steel mesh to form a wrinkled structure and multiple micro-nanoparticles on the stainless steel mesh to improve the hydrophilicity.

[0062] The embodiment of the present invention provides a temperature averaging plate, which includes a liquid wick prepared by the manufacturing method of the embodiment of the present invention. Specifically, the temperature averaging plate can be applied to various electronic devices such as smart phones, smart watches, and tablet computers.

[0063] The temperature homogenizing plate provided in the embodiment of the present invention has at least the following beneficial effects:

[0064] By adding the liquid absorbent core prepared by the manufacturing method according to the embodiment of the present invention to the temperature averaging plate, the temperature averaging plate can obtain higher heat dissipation efficiency without changing its volume, and can better adapt to the increasingly higher heat dissipation requirements.

[0065] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A method for making a liquid-absorbing core, characterized in that: include: Stainless steel mesh is provided; The surface of the stainless steel mesh is scanned by a laser, so that a wrinkled structure and a plurality of micro-nano particles are formed on the surface of the stainless steel mesh.

2. The method according to claim 1, characterized in that: The laser scans the surface of the stainless steel mesh 1 to 7 times.

3. The method according to claim 1, characterized in that: The laser pulse width of the laser is 1 μs-120 μs.

4. The method according to claim 1, characterized in that: The frequency of the laser is 80KHz-300KHz.

5. The method according to claim 1, characterized in that: The scanning speed of the laser is 1000mm / s-15000mm / s.

6. The method according to claim 1, characterized in that: Before the surface of the stainless steel mesh is scanned by a laser, the method includes: The stainless steel mesh was ultrasonically cleaned.

7. The manufacturing method according to claim 6, characterized in that: After the ultrasonic cleaning of the stainless steel mesh, the method comprises: The stainless steel mesh is dried.

8. The manufacturing method according to claim 1, characterized in that: The stainless steel mesh provided comprises: The stainless steel mesh was cut into the shape of a wick.

9. The manufacturing method according to claim 1, characterized in that: The particle size of the micro-nano particles is less than 500 μm.

10. A temperature equalizing plate, characterized in that: The invention comprises a liquid absorbent core prepared by the preparation method according to any one of claims 1 to 9.